2011
DOI: 10.1007/s00167-011-1620-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle activity around the knee and gait performance in unicompartmental knee arthroplasty patients: a comparative study on fixed- and mobile-bearing designs

Abstract: Retrospective comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 37 publications
1
49
1
Order By: Relevance
“…More sensitive outcome scores are needed. Gait analysis could provide more objective parameters, such as measurements of sagittal plane kinematics and kinetics (Börjesson et al 2005, Catani et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…More sensitive outcome scores are needed. Gait analysis could provide more objective parameters, such as measurements of sagittal plane kinematics and kinetics (Börjesson et al 2005, Catani et al 2012). …”
Section: Discussionmentioning
confidence: 99%
“…54 Furthermore, very small differences were found between the two designs on gait analysis. 55 With respect to patients' perceptions of UKAs, Bhattacharya et al noted that 83.5% of patients with fixed-bearing UKAs were satisfied compared with 93.9% of those with mobile-bearing UKAs. 56 Lateral versus Medial UKA…”
Section: Fixed Versus Mobile Bearingmentioning
confidence: 99%
“…Earlier research found that total knee arthroplasty (TKA) influences gait parameters [3,5,6,12,27,29,37,38,40] and the variability and stability of gait [14,31,41] 1 year after surgery. The measurement of gait patterns provides valuable information; however, it ignores the variability involved in the completion of the gait.…”
Section: Introductionmentioning
confidence: 99%